2017
DOI: 10.1002/asmb.2294
|View full text |Cite
|
Sign up to set email alerts
|

Reliability modelling incorporating load share and frailty

Abstract: The stochastic behaviour of lifetimes of a two component system is often primarily influenced by the system structure and by the covariates shared by the components. Any meaningful attempt to model the lifetimes must take into consideration the factors affecting their stochastic behaviour. In particular, for a load share system, we describe a reliability model incorporating both the load share dependence and the effect of observed and unobserved covariates. The model includes a bivariate Weibull to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Since 2006, some studies on reliability have used the frailty model for modeling the impact of unobservable risk factors on the reliability of the components, intending to make decisions about maintenance and repair [20][21][22][23]. For example, Asha [24] employed the frailty model for a load-sharing system and demonstrated that the reliability analysis for a heterogeneous case varies significantly compared to a homogeneous one. Asfaw and Lindqvist [25] utilized the frailty model for modeling the effect of observable and unobservable risk factors on wind turbine reliability, using Poisson's process.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2006, some studies on reliability have used the frailty model for modeling the impact of unobservable risk factors on the reliability of the components, intending to make decisions about maintenance and repair [20][21][22][23]. For example, Asha [24] employed the frailty model for a load-sharing system and demonstrated that the reliability analysis for a heterogeneous case varies significantly compared to a homogeneous one. Asfaw and Lindqvist [25] utilized the frailty model for modeling the effect of observable and unobservable risk factors on wind turbine reliability, using Poisson's process.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large number of possible extensions of this current work. The proposed IGP frailty model can be extended to other distributions for frailty, for example, we may assign the Weibull distribution for frailty, following a similar approach as in Asha et al 41 ; the Birnbaum‐Saunders distribution can also be considered for frailty, as discussed in Leão et al 42 . Our approach should be investigated further in these contexts.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in the presence of observable and unobservable risk factors, the frailty model can be used. Originally, this was developed by Asha et al [34] into load share systems and described the effect of observable and unobservable covariates on the reliability analysis. In later years, authors such as Xu and Li, Misra et al, and Giorgio et al discussed the properties of the frailty model [35][36][37].…”
Section: Methodology and Framework: Risk Factor-based Reliability Importance Measure (Rf-rim)mentioning
confidence: 99%